Incomplete loss of a conserved trait: function, latitudinal cline, and genetic constraints. (1st December 2016) - Royer, Anne M.; Kremer, Colin; George, Kola; Pérez, Samuel G.; Schemske, D. W.; Conner, Jeffrey K.
Abstract: Retention of nonfunctional traits over evolutionary time is puzzling, because the cost of trait production should drive loss. Indeed, several studies have found nonfunctional traits are rapidly eliminated by selection. However, theory suggests that complex genetic interactions and a lack of genetic variance can constrain evolution, including trait loss. In the mustard family Brassicaceae the conserved floral condition includes four long and two short stamens, but we show that short stamens in the highly self‐pollinating mustard Arabidopsis thaliana do not significantly increase selfed seed set, suggesting that the trait has lost most or all of its function after the transition to selfing. We find that short stamen loss is common in native populations. Loss is incomplete and decreases with increasing latitude, a cline unexplained by correlations with flowering time or ovule count (which also vary with latitude). Using recombinant inbred lines derived from a cross between plants at the latitudinal extremes of the native range, we found three QTLs affecting short stamen number, with epistasis among them constraining stamen loss. Constraints on stamen loss from both epistasis and low genetic variance may be augmented by high selfing rates, suggesting that these kinds of constraints may be common in inbred species.